Avskrift av dagbok ført under overvintringen på Østgrønland 13. april til 19. august 1931 - Karlsbak, Jonas; Røbek, Knut; Andresen, Hermann H.; Røbek, Peder; Sulebak, Peder; Aambak, Oddmund (1931)
DAG-144